Education in France during the interwar period and Front Populaire’s reforms (1919-1939) - Ostenc, Michel (Rivista di Storia dell’Educazione, 2017)
The French teaching of the inter war years (1918-1939) obey to traditional pedagogy and the teaching profession was imprisoned by corporative reflexes. The primary education succeed in social integration office and the secondary school used classical studies to form the elites of nation at Cartesian humanism; but the population growth was taked the necessary measures. The recruiting of the secondary school was indispensable. The success of children’s organizations was agreed to anti intellectual’s sensation and open nature life.